Electrolyte Chemistry Enables Simultaneous Stabilization of Potassium Metal and Alloying Anode for Potassium‐Ion Batteries. Issue 46 (26th September 2019) - Wang, Hua; Yu, Dandan; Wang, Xiao; Niu, Zhiqiang; Chen, Mengxue; Cheng, Liwei; Zhou, Wei; Guo, Lin
Abstract: Alloying anodes are promising high‐capacity electrode materials for K‐ion batteries (KIBs). However, KIBs based on alloying anodes suffer from rapid capacity decay due to the instability of K metal and large volume expansion of alloying anodes. Herein, the effects of salts and solvents on the cycling stability of KIBs based on a typical alloying anode such as amorphous red phosphorus (RP) are investigated, and the potassium bis(fluorosulfonyl)imide (KFSI) salt‐based carbonate electrolyte is versatile to achieve simultaneous stabilization of K metal and RP electrodes for highly stable KIBs. This salt‐solvent complex with a moderate solvation energy can alleviate side reactions between K metal and the electrolyte and facilitate K + ion diffusion/desolvation. Moreover, robust SEI layers that form on K metal and RP electrodes can suppress K dendrite growth and resist RP volume change. This strategy of electrolyte regulation can be applicable to other alloying anodes for high‐performance KIBs. Abstract : Of salts and solvents : Alloying anodes universally exhibit poor cycling performance for K‐ion storage due to the degradation of highly active K metal and the large volume expansion. It is revealed that the regulation of electrolyte chemistry is a feasible approach to simultaneously stabilize K metal and alloying anodes for realizing high‐performance K‐ion batteries based on alloying anodes.